2020
DOI: 10.1371/journal.pone.0240032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality of evidence for gaming disorder: A summary of systematic reviews of associations between gaming disorder and depression or anxiety

Abstract: Gaming disorder has been described as an urgent public health problem and has garnered many systematic reviews of its associations with other health conditions. However, review methodology can contribute to bias in the conclusions, leading to research, policy, and patient care that are not truly evidence-based. This study followed a pre-registered protocol (PROSPERO 2018 CRD42018090651) with the objective of identifying reliable and methodologically-rigorous systematic reviews that examine the associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…Given this, it is critical to understand that the quality of the evidence underlying possible classifications of video game play as potentially psychopathological has been criticized strongly. Many experts have argued that there is insufficient evidence that gaming disorder definitions and diagnostic tools meet clinical standards [15,[17][18][19][20][21][22]. Excessive use has been flagged as a key criterion for many gaming disorder definitions, yet researchers exclusively operationalize excessive use by way of selfreported estimates.…”
Section: Video Game Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this, it is critical to understand that the quality of the evidence underlying possible classifications of video game play as potentially psychopathological has been criticized strongly. Many experts have argued that there is insufficient evidence that gaming disorder definitions and diagnostic tools meet clinical standards [15,[17][18][19][20][21][22]. Excessive use has been flagged as a key criterion for many gaming disorder definitions, yet researchers exclusively operationalize excessive use by way of selfreported estimates.…”
Section: Video Game Behaviourmentioning
confidence: 99%
“…Work by Elson & Przybylski [35] showed that this issue arises regularly in research focused on the effects of technology, including in video games research. Carras et al [19] summarized systematic reviews on gaming disorder and found a high degree of selective reporting in the literature. To increase public trust in their findings, scientists have an obligation to work as transparently as possible, particularly when they collaborate with industry [36].…”
Section: Video Game Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this, it is critical to understand that the quality of the evidence underlying possible classifications of video game play as potentially psychopathological has been criticised strongly. Many experts have argued that there is insufficient evidence that gaming disorder definitions and diagnostic tools meet clinical standards (Aarseth et al, 2016;Abendroth et al, 2020;Bean et al, 2017;Carras et al, 2020;Kardefelt-Winther et al, 2017;Zastrow, 2017). Excessive use has been flagged as a key criterion for many gaming disorder definitions, yet researchers exclusively operationalise excessive use by way of self-reported estimates.…”
Section: Video Game Behaviourmentioning
confidence: 99%
“…In the addictive gaming behaviors literature, perhaps the most systematic finding of systematic reviews (e.g., Costa & Kuss, 2019;Colder Carras et al, 2020;King et al, 2020b) is that the field operates with a great range of heterogeneous and inconsistent survey instruments. As this "diagnostic confusion" ) strongly characterized the field already at the time of the DSM-5's release (King et al, 2013b), the descriptions provided by the DSM-5 and the ICD-11 were important as an opportunity to make the field more consistent and coherent, in terms of operationalized criteria at least.…”
Section: Discussionmentioning
confidence: 99%